PROGRAM DERADIKALISASI NARAPIDANA TERORISME DI LEMBAGA PEMASYARAKATAN KELAS IIB CILACAP: PROSES PERJALANAN MENUJU IKRAR SETIA NKRI - Abdullah, Sulthan; Yuska, Syahrial (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The threat of terrorism in Indonesia has evolved into a multidimensional problem that demands an approach not only legally but also socially and ideologically. As a follow-up to these threats, the penitentiary system has a strategic role in fostering terrorism inmates through deradicalization programs. This study aims to describe the process of implementation of the program of deradicalization of prisoners of terrorism in prison Class IIB Cilacap, as well as identify obstacles and challenges in its implementation. Using a descriptive qualitative approach, data was obtained through observation, interviews with key informants, and official documentation. The results showed that the deradicalization program in Cilacap Class IIB prison was implemented through a multidimensional approach: spiritual, ideological, psychosocial, and reintegrative. The success of the two inmates in declaring the Pledge of allegiance to the Republic of Indonesia proves the effectiveness of the program. However, the program faces challenges in the form of limited human resources, sectoral egos between institutions, as well as resistance from the community to the reintegration of ex-prisoners of terrorism. Intensive collaboration and strengthening of regulations and public education are needed to support the long-term success of this program.Keywords: deradicalization, terrorism inmates, Cilacap prison, NKRI pledge, Correctional.